2006
DOI: 10.1136/jnnp.2006.100016
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of gait by chronic, high doses of methylphenidate in patients with advanced Parkinson's disease

Abstract: Background: Therapeutic management of gait disorders in patients with advanced Parkinson's disease (PD) can sometimes be disappointing, since dopaminergic drug treatments and subthalamic nucleus (STN) stimulation are more effective for limb-related parkinsonian signs than for gait disorders. Gait disorders could also be partly related to norepinephrine system impairment, and the pharmacological modulation of both dopamine and norepinephrine pathways could potentially improve the symptomatology. Aim: To assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
85
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(89 citation statements)
references
References 32 publications
2
85
0
2
Order By: Relevance
“…Based on footfalls recorded on the walkway, the software automatically computes gait parameters such as gait speed (cm/s). The GAITRite system is widely used in clinical and research settings, and excellent reliability has been reported in our and other centers (Devos et al 2007;Verghese et al 2007a;Verghese et al 2007b). Research assistants also measured time in seconds to climb up three steps, a quick and valid clinical measure for assessing risk of functional decline (Oh-Park et al 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Based on footfalls recorded on the walkway, the software automatically computes gait parameters such as gait speed (cm/s). The GAITRite system is widely used in clinical and research settings, and excellent reliability has been reported in our and other centers (Devos et al 2007;Verghese et al 2007a;Verghese et al 2007b). Research assistants also measured time in seconds to climb up three steps, a quick and valid clinical measure for assessing risk of functional decline (Oh-Park et al 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Some small, open-label pilot studies suggested that a low dose methylphenidate may improve gait, and especially freezing, in patients with severe PD, without the need for exogenous levodopa. [99][100][101] This result was not confirmed by other trials 102,103 A recent randomized, placebo-controlled, double-blind 6-month trial showed that methylphenidate in doses up to 80 mg per day did not improve gait and tended to worsen measures of motor function, sleepiness, and quality of life. 104 Atomoxetine is a selective inhibitor of norepinephrine uptake and a small study failed to find significant benefits in gait and balance scores in PD.…”
Section: Noradrenergic Pharmacotherapy and Mobility In Pdmentioning
confidence: 49%
“…The effects of MPH on motor deficits are somewhat controversial. Some small, open, pilot studies demonstrated that a low dose may improve gait, and especially freezing, in patients with severe PD, without the need for exogenous levodopa [33][34][35]. However, this was not confirmed by other trials [36,37], including one set up in 2007.…”
Section: Methylphenidate (Mph)mentioning
confidence: 91%